Processo de implantação do acolhimento com classificação de risco no setor de urgências da clínica de odontologia da UEM - Padilha, Luciene Silvério (2012)
The organization of the attendance of the demand that looks for health service by using a risk classification demonstrates that it is suitable instrument for comply the SUS principles. It allows giving views to equity principle favoring attention integrity without compromising the universality principle. This work refers to the implementation of a change proposal for the Urgency Service (US) work process of the Dental Clinic (DC) at the State University of Maringá (UEM) with implementation of the Embracement with Risk Rating (URR). To achieve this aim, various risk rating, specific or not to Dentistry were compiled, by means of literature, and discussed. The literature review, epidemiological data collected at US/DC, and meetings with pacts among different participants, guided and enabled the creation of a specific risk rating instrument adapted to the Service reality, as well as to the flow chart of entrance door. The skills of workers who were directly linked to the urgency care were developed in order to facilitate the plan implementation. This was done by means of workshops which focused on improving the level of information, evaluation and problematization of the work process, sensibilization to user?s assistance care, and operationalization of the risk rating process itself. Preliminary assessment was conducted to verify: the user?s and sector attendance profiles in the post-intervention period, resolvability achieved, frequency of the classified priorities according to the risk posed, and length of waiting and of attendance. It was found quantitative improvements in the reduction of inadequate forms filling, in the predominance of compliance to clinical presentations considered of urgent care, in the expansion of the users referred for dental treatment schedule and in the registration of cases considered as discharge. Also, great achievements that should be considered are the qualitative improvement observed in the work process for servers and academics, as well as in the attention to the user. The reported experience may be used as a model for both public and private clinical services, and educational institutions. In view of problems as the unmet demand at the urgency services, and the dental care assistance access, the URR at US contributed to care assistance integrality and to exercise the universality, accessibility, bonding and continuity, accountability, humanization, equity and social participation.